Prominences in SDO/EVE spectra: contributions from large solar structures. Issue Volume 8:Issue S300(2013) (6th January 2014) - Labrosse, Nicolas; Hudson, Hugh; Kazachenko, Maria
Abstract: The EVE instrument on SDO is making accurate measurements of the solar spectral irradiance in the EUV between 30 and 1069 Å, with 1 Å spectral resolution and 10 s sampling rate. These data define solar variability in the "Sun-as-a-star" mode and reveal many interesting kinds of variation. Its high sensitivity also makes it suitable for spectroscopic diagnostics of solar features such as flares. Here we present EVE's potential contribution to the diagnostics of large-scale, slowly evolving features such as prominences and active regions, and what we can learn from this.